(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the impact of human resource management practices (recruitment and appointment, training and development, motivation, and performance evaluation) on employee performance at the Higher Institute of Science and Technology - Al-Aziziyah. The study adopted a descriptive-analytical approach and used a questionnaire as a data collection tool. Due to the limited population, a comprehensive survey was conducted, distributing 36 questionnaires. The study data was analyzed and its hypotheses tested using the SPSS statistical software. The study reached several conclusions, the most important of which was: the existence of a statistically significant impact of human resource management practices combined, which include (recruitment and appointment, training and development, motivation, and performance evaluation), on employee performance at the Higher Institute of Science and Technology - Al-Aziziyah This confirmed the study’s main hypothesis. The results also showed a positive correlation between these practices and performance; any improvement in the application of human resources practices was accompanied by a noticeable increase in the performance of employees at the Al-Aziziyah Higher Institute of Science and Technology.